Effect of silver ions on the optical properties of colloidal solutions of CdS/L-Cysteine nanoparticles - Krupko, O.; Shcherbak, L.P.; Khalavka, Yu.B.; Pylypko, V.G. (Physics and Chemistry of Solid State, 2024)
The synthesis of CdS/Ag+ heterostructures was carried out based on colloidal solutions of CdS nanoparticles stabilized by the amino acid L-cysteine ​​by the method of ion substitution and co-precipitation from aqueous solutions at room temperature and a hydrogen index value of 7. The effect of argentum ions on the optical properties of colloidal solutions of cadmium sulfide nanoparticles in the conditions of an oxidizing environment was investigated. Argentum ion concentrations were determined, the introduction of which leads to an increase in the photoluminescence of the system and the growth of nanoparticles compared to the original colloidal solution of CdS/L-Cysteine ​​NPs.